The Big Tent : The Traveling Circus in Georgia, 1820-1930 - Renoff, Greg, 1969- (Book collections on Project MUSE., 2008)
"Ranging across a changing social, cultural, and economic landscape, The Big Tent tells a new history of what happened when the circus came to town, from the time it traveled by wagon and river barge through its heyday during the railroad era and into its final decline in the age of the automobile and mass consumerism."--Jacket.